Ampicillin Treatment of Intracellular Listeria monocytogenes Triggers Formation of Persistent, Drug-Resistant L-Form Cells - Grosboillot, Virginie; Keller, Isabelle; Ernst, Chantal; Loessner, Martin J.; Schuppler, Markus (Frontiers in Cellular and Infection Microbiology, 2022)
Listeria monocytogenes is an opportunistic intracellular pathogen causing an infection termed listeriosis. Despite the low incidence of listeriosis, the high mortality rate in individuals at risk makes this bacterium one of the most dangerous foodborne pathogens. Reports about a relapse of infection after antibiotic treatment suggest that the bacteria may be able to evade antibiotic treatment and persist as a dormant, antibiotic-tolerant subpopulation. In this study, we observed intracellular generation of antibiotic-resistant L-forms of Listeria monocytogenes following Ampicillin treatment of Listeria monocytogenes infected cells. Detection and identification of intracellular Listeria L-forms was performed by a combination of fluorescence in-situ hybridization and confocal laser scanning microscopy. Using micromanipulation, it was possible to isolate single intracellular L-form cells that following transfer into fresh medium gave rise to pure cultures. In conclusion, the results obtained here provide strong evidence that antibiotic treatment of infected host cells can induce the formation of L-forms from intracellular Listeria monocytogenes. Furthermore, our results suggest that intracellular L-forms persist inside host cells and that they represent viable bacteria, which are still able to grow and proliferate.